Towards fast and low cost Sb2S3 anode preparation: A simple vapor transport deposition process by directly using antimony sulfide ore as raw material. (December 2019) - Wang, Qi; Liu, Fangyang; Wang, Li; Jiang, Liangxing; Wang, Qiyu; Hong, Bo; Lai, Yanqing
Abstract: Traditional preparation of Sb2 S3 anode requires a long and complex process and high cost, which is difficult to realize commercialization. To overcome this challenge, we demonstrate a compact vapor transport deposition (VTD) process to prepare Sb2 S3 thin-film anode from antimony sulfide ore. This VTD Sb2 S3 anode show well crystallized nanosheets with porous microstructures and exhibit good cyclicality and high rate performance. The results indicate that this process is feasible and practical for simplifying Sb2 S3 anode preparation. Graphical abstract: Unlabelled Image